从《官话类编》看汉语书面语的历时演变 = A study of the diachronic development of written Chinese based on a course of Mandarin lessons - 李宛芯 Lee, Wan Xin (2010)
朱德熙（1987）认为，“现代汉语书面语包含许多不同的层次，稳定性和均匀性都远不如北京口语。”冯胜利（2003）则提出，“现代汉语书面语语法的独立性：它既区别于文言，也不同于口语，而是一种相对独立的语法体系。”根据两位学者的意见，我们知道书面语不是口语的直接反映。现代汉语书面语虽然层次复杂，但却依旧有一套规范。从历时的角度看，这套规范又和官话方言（北方方言）有着密切的关系。根据鲁国尧（1985）、张卫东（1998）、平田昌司（2000）等的研究，我们知道南方官话和北方官话虽然同属官话，但是在近代它们的影响力却有消长的现象，这种官话方言内部影响力的消长是否也体现在书面语上，是我们这篇论文希望探讨的。Zhu Dexi (1987) commented that given the many layering aspects within the Modern Chinese written language, it is not comparable to the Peking spoken language in terms of stability and uniformity. Feng Shengli (2003) has also suggested that the grammar of written Chinese must be considered an independent system from both the modern spoken Chinese and the classical literary. According to the opinions of both scholars; the written language is not a reflection of the spoken language. In spite of its complexity, there are certain norms in the Modern Chinese Written Language to be adhered to. Looking from a historical perspective, the norms of the Modern Chinese Written Language are closely related to Mandarin, which is the Northern Mandarin. According to Lu Guoyao (1985), Zhang Weidong (1998), Pingtian Changsi (2000), Southern Mandarin and Northern Mandarin, both comes under the large umbrella of Mandarin. However, there are signs of growth and decline of their influence in the pre modern period. This thesis aims to find out if such a phenomenon is also reflected in the written language. The research methodology is as such. In the 19th century, C. W. Mateer wrote a textbook A course of Mandarin Lessons, for westerners who wish to learn Mandarin. In this book, he clearly introduced and differentiated the colloquialism and localisms of Northern Mandarin and Southern Mandarin (refer to Zhang Min 1995). It is closely related to the changes of the subdialects.